An inverting β‐1, 2‐mannosidase belonging to glycoside hydrolase family 130 from Dyadobacter fermentans. Issue 23 (20th October 2015) - Nihira, Takanori; Chiku, Kazuhiro; Suzuki, Erika; Nishimoto, Mamoru; Fushinobu, Shinya; Kitaoka, Motomitsu; Ohtsubo, Ken'ichi; Nakai, Hiroyuki
Abstract : The glycoside hydrolase family (GH) 130 is composed of inverting phosphorylases that catalyze reversible phosphorolysis of β‐d ‐mannosides. Here we report a glycoside hydrolase as a new member of GH130. Dfer_3176 from Dyadobacter fermentans showed no synthetic activity using α‐d ‐mannose 1‐phosphate but it released α‐d ‐mannose from β‐1, 2‐mannooligosaccharides with an inversion of the anomeric configuration, indicating that Dfer_3176 is a β‐1, 2‐mannosidase. Mutational analysis indicated that two glutamic acid residues are critical for the hydrolysis of β‐1, 2‐mannotriose. The two residues are not conserved among GH130 phosphorylases and are predicted to assist the nucleophilic attack of a water molecule in the hydrolysis of the β‐d ‐mannosidic bond. Abstract : A β‐mannosidase acting on β‐1, 2‐mannooligosaccharides was discovered. The enzyme is the first hydrolase belonging to GH130 of β‐mannoside phosphorylases. Two Glu residues assisting nucleophilic attack of a water molecule were identified.